Central Administration of 5Z-7-Oxozeaenol Protects Experimental Autoimmune Encephalomyelitis Mice by Inhibiting Microglia Activation - Lu, Lingli; Zhang, Xiuping; Tong, Huichun; Zhang, Wenlong; Xu, Pingyi; Qu, Shaogang (Frontiers in Pharmacology, 2017)
Transforming growth factor β-activated kinase 1 (TAK1), a vital upstream integrator of multiple pro-inflammatory signaling pathways, mediates the production of pro-inflammatory cytokines, chemokines, and adhesion molecules. Investigations targeting TAK1 provide new therapeutic options for chronic inflammatory disorders, autoimmune diseases and cancer. However, the role and mechanism of the TAK1 inhibitor 5Z-7-oxozeaenol in treating autoimmune demyelinating diseases remain unclear. This work aimed to identify whether 5Z-7-oxozeaenol exerts neuroprotective effects on experimental autoimmune encephalomyelitis in mice. Here, we demonstrate that 5Z-7-oxozeaenol efficiently alleviates the symptoms of experimental autoimmune encephalomyelitis by decreasing the levels of pro-inflammatory cytokines in splenocytes and central nerve system, diminishing the number of activated microglia and inhibiting the p38MAPK, JNK and ERK signaling pathways. Furthermore, we demonstrate that administration during the symptomatic time window is required for 5Z-7-oxozeaenol efficacy. These results suggest that TAK1 inhibition may provide a potent approach towards treating autoimmune demyelinating diseases.